Nominal Formations and Defining Headwords in the Reverse Version of Hippolytus’s Dictionary - Jelovšek, Alenka (Jezikoslovni zapiski, 2023)
This article presents the issue of defining headwords for selected nominal formations (derivatives from verbal calques, compounds with a deadverbial prefix, and compounds) in the reverse version of the dictionary by Hippolytus of Novo Mesto (Hippolytus Rudolphswertensis) based on whether they are written together or separately. The coverage of selected examples of these formations is compared across Slovenian historical dictionaries, and dilemmas in defining headwords, especially the issue of distinguishing compounds from word combinations with a nominal modifier in an atypical position, are highlighted based on the material used for the reverse dictionary.